Analgesic impact of buprenorphine transdermal patch in total hip arthroplasty: A randomized controlled trial protocol. Issue 24 (12th June 2020) - Li, Wen-Min; Li, Feng-Dao; Xu, Hua; Sun, Li-Chen
Abstract: Background: The efficacy and safety of buprenorphine transdermal patch (BTP) has been well established in chronic pain, but data regarding acute postoperative pain relief is still very limited. Therefore, we design a prospective, randomized, controlled study to evaluate the effectiveness and safety of the BTP for postoperative analgesia in total hip arthroplasty. Methods: This study is designed as a single-center, prospective, double-blind, randomized controlled trial. Group A receives a 10 mg patch of buprenorphine at the conclusion of surgery which is continued for 14 days. Group B receives a conventional analgesic regimen, that is, IV paracetamol 1 mg every 8 hours alternating with parenteral tramadol 50 mg every 8 hours for the first 2 postoperative days followed by oral administration of the same drug still the end of 2 weeks. A total of 160 patients are needed with an allowance for 10% drop-out. The primary outcome of this noninferiority study is opioid consumption within the first 24 hours following surgery. The secondary outcomes included numerical rating scale scores at rest, postoperative complications, length of hospital stay, and patient satisfaction. Results: This trial is expected to be the largest randomized trial assessing the efficacy of BTP after primary total hip arthroplasty and powered to detect a potential difference in the primary outcome. Trial registration number: This study protocol was registered in Research Registry (researchregistry5524).